Maternal Cardiovascular Adaptations in Normal and Complicated Pregnancy - Amir Khan, Mohammad; Hussain, Asma; Rahim, Fouzia; Afridi, Saleha; Faisal, Sanober; Zaheer, Aysha (Journal of Neonatal Surgery, 2025)
Background: Pregnancy induces profound cardiovascular changes to support maternal and fetal metabolic demands. Normal adaptations include increased blood volume, cardiac output, and heart rate, with decreased systemic vascular resistance. In complicated pregnancies such as preeclampsia and gestational hypertension, these adaptations may be impaired, increasing maternal and fetal risk. Objective: To evaluate maternal cardiovascular adaptations in normal versus complicated pregnancies and quantify the prevalence of maladaptive changes. Methods: A cross-sectional observational study was conducted on n = 200 pregnant women (120 normal, 80 complicated) at 28–36 weeks gestation. Cardiovascular parameters measured included heart rate, blood pressure, cardiac output, and echocardiographic indices (left ventricular mass, stroke volume). Data were analyzed using descriptive statistics and compared using Student’s t-test and chi-square test; p < 0.05 was considered significant. Results: In normal pregnancies, mean cardiac output increased by 35% and stroke volume by 30% compared to pre-pregnancy values. Heart rate increased by 18% and systemic vascular resistance decreased by 20%. In complicated pregnancies, 65% exhibited elevated mean arterial pressure (>95 mmHg), 48% showed left ventricular hypertrophy, and 52% had reduced stroke volume (<50 mL). Differences between groups were statistically significant (p < 0.01). Maternal symptoms such as edema and dyspnea were reported in 42% of complicated pregnancies versus 12% in normal pregnancies. Conclusion: Maternal cardiovascular adaptations are essential for healthy gestation. Complicated pregnancies show significant deviations from normal hemodynamic patterns, with higher prevalence of hypertension, ventricular remodeling, and reduced stroke volume. Early identification and monitoring of these maladaptive changes are crucial for optimizing maternal and fetal outcomes and reducing long-term cardiovascular risk